Research Progress in the Bitterness Mechanism and Debittering Strategies of Bitter Peptides - PU Minghui, WU Hao, WEN Li, CHEN Maolong, CHENG Yunhui (Shipin Kexue)
Bitter peptides derived from the hydrolysis of proteins can cause food to taste bitter and are generally deemed undesirable from the perspective of taste. However, studies have shown some bitter peptides to have bioactivities that are beneficial to human health and helpful for alleviating chronic diseases. Hence, elucidating the bitter mechanism of bitter peptides is important for improving the taste and bioactivity utilization of food. Previous studies have pointed out the factors affecting the bitterness of peptides, such as Q value, bitter amino acids, bitterness indicator motifs and spatial structure, but the universal mechanism is still unclear. Enzymatic and non-enzymatic debittering treatments have been developed for laboratory and industrial applications, among which, enzymatic debittering treatments have attracted more attention due to the high efficiency and biosafety, and animal/plant/microorganism-derived enzymes with debittering capacity or potential have been identified and reported continuously. This review comprehensively summarizes recent progress in bitter peptides, including their sources, bioactivities, identification methods, bitterness mechanism and enzymatic/non-enzymatic debittering treatments, and the common characteristics of enzymes from different sources with debittering capacity or potential. Finally, it gives an outlook on future research directions.